Praktik Pariwisata Berbasis Masyarakat dalam Pengembangan Pariwisata Pedesaan: Studi Kasus Taman Wisata Alam Egon, Kabupaten Sikka, Provinsi Nusa Tenggara Timur - Michael Rudolfus Sawu; Natalia Kristiani Tandafatu; Desiderius Siga Meli Poa (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study aims to analyse the practices of community-based tourism development, the level of community participation and to formulate a collaborative development model to strengthen its management system. A qualitative approach with a case study design is employed. The researcher conducted observations of community-based tourism practices, in-depth interviews with local residents and a review of relevant literature. The collected data will be analysed using a descriptive qualitative method. The data will be reduced, verified, and concluded based on the analysis carried out. The research findings indicate that although there is considerable potential for adventure tourism, there are still significant shortcomings in its development. Therefore, a collaborative development pathway is needed to enhance the management system in the future, so as to generate meaningful social implications for the local community.